PENGARUH ION Cr (VI) TERHADAP FOTODEGRADASI - One Hartawati, ; Rusmini, (Matematika dan Sains, 2010)
Study about effect of Cr (IV) ion concentration to methylene blue photodegradation catalyzed by TiO2 had been done. Photodegradation process was conducted at closed reactor radiated by UV lamp with type B 40 Watt using bath system. The suspency consisting of methylene blue solution, TiO2 powder, and K2Cr2O7 solution were radiated by UV lamp a long with stirring for certain time. Undegradated methylene blue concentration was measured using UV-Vis spectrophotometer, while effect of Cr (VI) ion was determined with comparing differentiated between initial and residual methylene blue concentration. The result of research showed that increasing of ratio of Cr (IV) ion concentration was decreased the degradation of methylene blue concentration. The higher methylene blue photodegradaton (59,660%) was obtained at methylene blue concentration of 10 mg/L, 50 mg of TiO2 in 50 mL solution, neutral pH, and radiation for 1 hour.2 had been done. Photodegradation process was conducted at closed reactor radiated by UV lamp with type B 40 Watt using bath system. The suspency consisting of methylene blue solution, TiO2 powder, and K2Cr2O7 solution were radiated by UV lamp a long with stirring for certain time. Undegradated methylene blue concentration was measured using UV-Vis spectrophotometer, while effect of Cr (VI) ion was determined with comparing differentiated between initial and residual methylene blue concentration. The result of research showed that increasing of ratio of Cr (IV) ion concentration was decreased the degradation of methylene blue concentration. The higher methylene blue photodegradaton (59,660%) was obtained at methylene blue concentration of 10 mg/L, 50 mg of TiO2 in 50 mL solution, neutral pH, and radiation for 1 hour.